Produksi Media Pembelajaran IPA "Perubahan Wujud Benda" Melalui Video Animasi BrainPOP dan Soal Interaktif untuk Kelas 4 SD - Isrowiyah Isrowiyah; Ika Putra Viratama (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
Science learning in elementary schools, especially regarding the material on changes in the state of matter, requires media that can present concepts in a concrete and interesting way so So that it is easy for students to understand. This research aims to develop a science learning medium about changes in the states of matter through BrainPOP animated videos equipped with interactive questions for fourth-grade elementary school students, and to evaluate the level of feasibility and studentThis research focuses on students’ feedback toward the developed learning media. It adopts a The research and development (R&D) methodology based on the ADDIE model includes steps such as needs analysis, instructional design, product development, implementation, and evaluation. The students involved in the research were in fourth grade  elementary school students, fourth-grade teachers, and validators from material experts and media experts. The process of data collection involved multiple methods such as direct observation, in-depth interviews, and the distribution of questionnaires obtained were analyzed using quantitative and qualitative descriptive techniques. The results of the study indicate that the developed learning media is classified as very feasible based on validation provided by material experts and media experts. In addition, the results of limited trials indicate that students gave a very positive response to the use of these learning media. Therefore, science learning media based on BrainPOP animated videos and interactive questions can be considered a feasible alternative to increase the interest and understanding of fourth-grade elementary school students.